2023
DOI: 10.3389/fneur.2023.1146164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perioperative cognitive function training on postoperative cognitive dysfunction and postoperative delirium: a systematic review and meta-analysis

Abstract: BackgroundRandomized controlled trials (RCTs) have shown conflicting results regarding the effects of perioperative cognitive training (CT) on the incidence of postoperative cognitive dysfunction (POCD) and postoperative delirium (POD). We, therefore, performed a meta-analysis to assess the overall effects of studies on this topic.MethodsWe searched PubMed, Embase, the Cochrane Library, and Web of Science for all RCTs and cohort studies that investigated the effects of perioperative CT on the incidence of POCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Current evidence suggests that drug interventions have an uncertain effect on cognitive impairment ( 11 , 12 ), so non-pharmacological interventions for POCD may be an effective means of prevention and a focus for future research. Many randomized controlled trials (RCT) and meta-analyses have shown that non-pharmacological interventions have a positive effect on the improvement and prevention of POCD ( 13 , 14 ). Therefore, our studies summarize the current non-pharmacological interventions of POCD from the aspects of cognitive training, physical activity, transcutaneous electrical acupoint stimulation, noninvasive brain stimulation, non-pharmacological sleep improvement, music therapy, environment, and multimodal combination Interventions, to provide more data for clinical application and research.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests that drug interventions have an uncertain effect on cognitive impairment ( 11 , 12 ), so non-pharmacological interventions for POCD may be an effective means of prevention and a focus for future research. Many randomized controlled trials (RCT) and meta-analyses have shown that non-pharmacological interventions have a positive effect on the improvement and prevention of POCD ( 13 , 14 ). Therefore, our studies summarize the current non-pharmacological interventions of POCD from the aspects of cognitive training, physical activity, transcutaneous electrical acupoint stimulation, noninvasive brain stimulation, non-pharmacological sleep improvement, music therapy, environment, and multimodal combination Interventions, to provide more data for clinical application and research.…”
Section: Introductionmentioning
confidence: 99%